World Drug Report 2014 - United Nations Office on Drugs; Crime (United Nations, 2014)
The World Drug Report presents a comprehensive overview of the latest developments in drug markets. It covers production, trafficking, consumption and the related health consequences. Chapter 1 of this year’s Report examines the global situation and the latest trends in the different drug markets and the extent of illicit drug use, as well as the related health impact. Chapter 2 addresses the issue of precursor control, which has gained in prominence given the growing manufacture of synthetic drugs.